Erosion Corrosion in the Oil and Gas Industry: A Review - Ige, O.O.; Umoru, L.E.; Olorunniwo, O.E.; Adeoye, M.O. (Ife Journal of Technology, 2011)
This paper reviews the various factors that affect erosion corrosion in the oil and gas industry. The mechanisms are highlighted and explained, with a view to understanding the underlying principle of the degradation phenomena. There are many monitoring techniques that are used in evaluating erosion corrosion but three are commonly employed in the laboratories. The benefits and limitations associated with these methods - rotated disc, rotated cylinder and jet impingement are reviewed. Erosion corrosion is regarded as a surface process that can be controlled via surface engineering for example, using coatings and inhibitors coupled with materials selection. Some of the critical parameters, such as inhibitor concentration as a function of flow parameters are discussed.